RELATIONSHIP BETWEEN ORGANIZATIONAL INTELLIGENCE AND HOSPITALS AGILITY OF SHIRAZ UNIVERSITY OF MEDICAL SCIENCES - CHAMAN, KHAIRALLAH; HESAM, SOMAYEH; YAZDANPANAH, ABBAS (International Journal of Clinical and Biomedical Research, 2016)
Introduction: Regarding the changing environment of hospitals and necessity of providing services in the shortest possible time and with acceptable quality and cost for patients, attention to innovative and smart approaches and using maximum mental abilities of the organization for increasing hospitals agility seems necessary. In fact, this study aims to answer this question that is there a significant relation between organizational intelligence (and its components according to Albrecht model) and hospitals agility?Method: The present study is applied in respect of aim and descriptive in regard of nature and method and for this purpose, a 368 persons sample was selected by stratifies sampling method among all 8247 personnel working in 15 active hospitals. For data collection in the field of organizational intelligence Albrecht organizational intelligence standard questionnaire and for organization agility, agility standard questionnaire which has been designed based on Goldman agility model were used. Results: Findings showed that there is a positive and significant relation between organizational intelligence and its seven components (strategic perspective, shared fate, desire to change, spirit, knowledge application, union and agreement and performance pressure) with hospitals agility and except intervening variable of educations other intervening variables like age, gender, marital status and working background have no impact on organizational intelligence and hospitals agility. Conclusion: Regarding the results of this study, choosing some solutions for codifying dynamic strategic programs in hospitals and holding training courses of organizational intelligence for informing personnel and managers could lead to increasing of hospitals agility level and providing effective service for patients.